Learning and memory in molecular networks - Lissek, Thomas (Biochemical and biophysical research communications, 2025)
The present work examines the capacity of biological systems to encode memories via adaptive changes in molecular networks. In single cells, the rewiring of molecular networks can store information as molecular engrams and instantiate learning processes. In multicellular organisms, single cells might communicate with each other and tune their molecular memories to cooperatively encode multicellular memories in tissues and organs. Learning in the whole brain might consequently be examined as a problem of individual cells learning how to form a memory together by tuning their single-cell memories to each other. A significant amount of memory content in the brain might hence be stored at the molecular level inside of single cells. Molecular memory formation is proposed as a universal concept to explain adaptive organism phenotypes and can elucidate memory phenomena in the brain, immune system, skeletal muscle, skin, endocrine system and during development among others. Consequently, the formation of maladaptive memories in different tissues can explain stable, environmentally-induced dysfunction in various human diseases including cancer, autoimmunity, addiction, post-traumatic stress disorder, obesity, diabetes and fibrosis. The targeting of physiological molecular memories and the creation of synthetic memories could be valuable strategies to influence organism physiology in biological engineering and therapeutic interventions.